Time limits and default judgments in European cross-border civil litigation: minimum standards? - Chiapponi, Giovanni (CUADERNOS DE DERECHO TRANSNACIONAL, 2020)
The article focuses on the impact of time limits on the free circulation of judgments rendered in absentia in civil and commercial matters within the EU. Starting from the Lebek judgment, I will examine the following issues: first, if an application for relief from the involuntary expiry of time limits may justify the denial of recognition and enforcement of judgments under the regime of the Brussels I bis Regulation; second, if the defendant applying for relief may choose between the time limit laid down in the service Regulation or that provided for in national law. Finally, I will address the question of the possible standardisation of the deadline for the first reaction on the part of the defendant.